PENGARUH TINGKAT BAGI HASIL DEPOSITO MUDHARABAH, FINANCING TO DEPOSIT RATIO, DAN SUKU BUNGA DEPOSITO TERHADAP PERTUMBUHAN DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH DI INDONESIA - Ruslizar, Ruslizar; Rahmawaty, Rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The objective of the research was to find out the influence of Mudharabah Deposit Revenue Sharing, Financing to Deposit Ratio, and Deposit Interest Rateon Mudharabah Deposit growth simultaneously and partially on TheIslamic Banks in Indonesia. The research used causal asosiative design. The population was 11Islamic Banks in Indonesia, and whole observed. The period of observation was since 2012 until 2014, so there were 33 analysis units all together. The data were processed by using multiple linear regression tests with an SPSS software program. The result of the research showed that mudharabah deposit revenue sharing, Financing to Deposit Ratio, and deposit interest rate both simultaneously and partially influenced Mudharabah Deposit Growth.Keywords: Mudharabah Deposit Revenue Sharing, Financing to Deposit Ratio, Deposit Interest Rate, Mudharabah Deposit Growth